Data on insect biodiversity in a Chinese potato agroecosystem from DNA metabarcoding - Changjin Lin; Chenxi Liu; Lilin Chen; Hongmei Cheng; Muhammad Ashfaq; Paul D. N. Hebert; Yulin Gao (Scientific Data)
Abstract Potato (Solanum tuberosum) is a staple crop important in global food security. As a leading potato producer, China faces significant challenges from insect pest infestations that compromise yield and quality. However, insect communities within Chinese potato fields remain poorly characterized. This study aimed to explore insect diversity in potato fields in Yunnan Province. From autumn 2021 to summer 2022, five Malaise traps were strategically deployed to capture insect samples. In total, 245 samples were collected over 49 weeks, and DNA metabarcoding was performed on bulk samples. The generated sequences were curated and analyzed using the Barcode of Life Data System and the Multiplex Barcode Research and Visualization Environment. The analysis assigned sequences to 1,688 Barcode Index Numbers (BINs) as species proxies derived from the Global Insecta Library, along with 166 BINs from the China Insecta dataset. This research provides valuable insights for barcoding local biodiversity and developing regional reference libraries and presents a comprehensive dataset of insect biodiversity within potato agroecosystems, encompassing 1,707 BINs linked to known insect taxa.